Sevoflurane Exposure Induces Neuronal Cell Parthanatos Initiated by DNA Damage in the Developing Brain via an Increase of Intracellular Reactive Oxygen Species - Piao, Meihua; Wang, Yingying; Liu, Nan; Wang, Xuedong; Chen, Rui; Qin, Jing; Ge, Pengfei; Feng, Chunsheng (Frontiers in Cellular Neuroscience, 2020)
The safety of volatile anesthetics in infants and young children has recently drawing more concerns due to its potential neurotoxicity in developing brain. Neuronal death is considered a major factor associated with developmental neurotoxicity after exposure to volatile anesthetics sevoflurane, but its mechanism remains elusive. Parthanatos, a new type of programmed cell death, resulting from poly (ADP-ribose) polymerase 1 (PARP-1) hyperactivation in response to DNA damage, was found to account for the pathogenesis of multiple neurological disorders. However, the role of Parthanatos in sevoflurane-induced neonatal neuronal cell death has not been investigated. To test, neuronal cells treated with 2%, 4%, 8% sevoflurane for 6 h, 12 h, 24 h and postnatal day 7 rats exposed to 2.5% sevoflurane for 6 h were used in the present study. Our results found sevoflurane exposure induced neuronal cell death, which was accompanied by PARP-1 hyperactivation, cytoplasmic polymerized ADP-ribose (PAR) accumulation, mitochondrial depolarization and apoptosis-inducing factor (AIF) nuclear translocation in neuronal cells and hippocampus of rats. Pharmacological or genetic inhibition of PAPR-1 significantly alleviated sevoflurane-induced neuronal cell death and accumulation of PAR polymer as well as AIF nuclear translocation, which were consistent with the features of Parthanatos. We observed in vitro and in vivo that sevoflurane exposure resulted in DNA damage given that 8-hydroxydeoxyguanosine (8-OHdG) and phosphorylation of histone variant H2AX (γH2AX) were improved. Moreover, we detected that sevoflurane exposure was associated with overproduction of intracellular reactive oxygen species (ROS). Inhibition of ROS with antioxidant NAC markedly alleviated DNA damage caused by sevoflurane, indicating that ROS participated in the regulation of sevoflurane-induced DNA damage. Additionally, sevoflurane exposure resulted in upregulation of Parthanatos-related proteins and neuronal cell death, which were significantly attenuated by pretreatment with NAC. Therefore, these results suggest that sevoflurane exposure induces neuronal cell Parthanatos initiated by DNA damage in developing brain via increase of intracellular ROS.